Investigation of monogenic causes of familial breast cancer: data from the BEACCON case-control study - Na Li (Nature Portfolio, 2021)
Abstract Breast cancer (BC) has a significant heritable component but the genetic contribution remains unresolved in the majority of high-risk BC families. This study aims to investigate the monogenic causes underlying the familial aggregation of BC beyond BRCA1 and BRCA2, including the identification of new predisposing genes. A total of 11,511 non-BRCA familial BC cases and population-matched cancer-free female controls in the BEACCON study were investigated in two sequencing phases: 1303 candidate genes in up to 3892 cases and controls, followed by validation of 145 shortlisted genes in an additional 7619 subjects. The coding regions and exon–intron boundaries of all candidate genes and 14 previously proposed BC genes were sequenced using custom designed sequencing panels. Pedigree and pathology data were analysed to identify genotype-specific associations. The contribution of ATM, PALB2 and CHEK2 to BC predisposition was confirmed, but not RAD50 and NBN. An overall excess of loss-of-function (LoF) (OR 1.27, p = 9.05 × 10−9) and missense (OR 1.27, p = 3.96 × 10−73) variants was observed in the cases for the 145 candidate genes. Leading candidates harbored LoF variants with observed ORs of 2–4 and individually accounted for no more than 0.79% of the cases. New genes proposed by this study include NTHL1, WRN, PARP2, CTH and CDK9. The new candidate BC predisposition genes identified in BEACCON indicate that much of the remaining genetic causes of high-risk BC families are due to genes in which pathogenic variants are both very rare and convey only low to moderate risk.